Uji Potensi Ekstrak Etil Asetat Daun Pepaya Jepang Cnidoscolus aconitifolius Terhadap Mortalitas Larva Nyamuk Aedes aegypti Instar III - Rahma Agustina; Emantis Rosa; Primasari Pertiwi; Sutyarso (CV. Multi Kreasi Media, 2026)
Dengue Hemorrhagic Fever (DHF) with the main vector Aedes aegypti requires an environmentally friendly control alternative using natural larvacides, such as Japanese papaya leaves (Cnidoscolus aconitifolius) which are rich in phytochemical compounds such as flavonoids, alkaloids, phenolics, saponins, tannins and steroids with potential as tannins and steroids. This study aims to determine the phytochemical content of Japanese papaya leaf ethyl acetate extract, to determine the potential of Japanese papaya leaf ethyl acetate extract as a larvicide against Aedes aegypti mosquito larvae, and to determine the relationship between the concentration of Japanese papaya leaf ethyl acetate extract and the mortality of Aedes aegypti larvae. The study method used a Completely Randomized Design (CRD) with 7 treatments of Japanese papaya leaf ethyl acetate extract 0.5%, 1%, 1.5%, 2%, 2.5%, 3% and 0% (control) with 4 replications. Observations were made by counting the number of larval deaths at 24 hours. To determine the effect of Japanese papaya leaf ethyl acetate extract on larval mortality, data were analyzed using the Kruskal-Wallis test. If significant, the data were then followed by Mann-Whitney test. A very strong correlation (Rs = 0.956) was found between concentration and mortality. It can be concluded that ethyl acetate extract of Japanese papaya leaves has the potential to be a natural larvicide for environmentally friendly dengue vector control.